Lie-Kac bigroups - Palyutkin, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We define the Lie-Kac bigroups as special double Hilbert algebras canonically associated with ring groups (the Kac algebras) and related to the Lie bialgebras.